THE EFFECTIVENESS OF USING STORY COMPLETION TECHNIQUE ON SPEAKING SKILL AT THE EIGHTH GRADE STUDENTS OF SMP ISLAM DARUSSA’ADAH MALANG IN THE ACADEMIC YEAR OF 2019/2020 - Ahmad Zainin Zahri Abu Aufa (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2020)
Abstract: The study aims to test the effectiveness of story completion techniques in developing speaking skills and overcoming a lack of confidence in the eighth grade of SMPI Darussa’adah Malang. The researcher used experimental research designs that used pre-test and post-test with quantitative approaches. The researcher took all eighth students as the population. The researcher used probability purposive sampling in determining the sample with 32 students from class 8a as experimental and control groups. The independent variable is the story completion technique and the dependent variable is students' speaking skills. The researcher compares pre-test and posttest results between two groups from inter-rater and used an independent SPSS t-test to analyze the data. The pre-test to posttest of experimental was 48.25 to 65.50, the control group was 46.63 to 57.13, and the p-value was 0.033, p= < 0.05. 0.05 was α (alpha) value. As a result, the researcher concluded that there was a significant effect of using story completion on students’ speaking skills. Finally, the researcher expects criticism and other suggestion for the development for much limited time and action because of COVID-19 also many shortages in her research.Keywords: effective, story completion technique, student speaking skill,